Consumers’ experience of security and expectations towards CSR communications in a crisis-stricken environment - Peltomäki, Paavo (My University, 2025)
Our social environment is becoming crisis-stricken due to various, simultaneous crisis processes. One effect of a crisis-stricken environment is a change in consumers’ experience of security. Consequently, consumers are increasingly demanding action from companies to curb the crises of our times, and at the same time, businesses are expected to meet these expectations with their CSR communications. The purpose of this study was to analyse consumers’ experience of security and how it reflects on consumer expectations towards corporate social responsibility communications in a crisis-stricken environment. The theoretical background of the study is based on consumer experience research and corporate social responsibility communications research, while also utilizing literature from the fields of psychology and sociology. For the study, 17 qualitative theme interviews were conducted. Based on the analysis, consumers’ experience of security in a crisis-stricken environment is constituted of five dimensions: the basic well-being pillars of life, stability, controllability, intrapersonal processing capability and emotional state. The consumers’ experience of security is also reflected in consumer expectations towards companies, meaning expectations of trustworthiness, meaningful actions and considerations of current environment. If organizations strive to meet the consumer expectations, their CSR communication should have elements of transparency, authenticity, stakeholder-orientation and established sustainability. The study has both theoretical and managerial value. The study highlighted the expectations consumers have towards companies holistically in a crisis-stricken environment and explored the driving factor behind the expectations, consumers’ experience of security. By increasing knowledge about consumers’ experience of security during times of crises, the study enriches the theoretical field of consumer experience. Additionally, the study explored how companies should meet consumer expectations by analysing the elements of an effective CSR communication strategy. Regardless of the state of the social environment, the tools for efficiently meeting consumer expectations are the same for companies. These findings also provide guidance for communication and management decision-making in companies. The most important contribution of the study is to bring to the limelight a topical phenomenon characterizing our time and encourage the scientific community to explore the phenomenon further.

Sosiaalinen ympäristömme on muuttumassa kriisiytyneeksi lukuisten samanaikaisten kriisiprosessien vuoksi. Yksi kriisiytyneen ympäristön seurauksista on muutos kuluttajien turvallisuuden kokemuksessa. Kuluttajat vaativatkin yhä enemmän toimia yrityksiltä aikamme kriisien hillitsemiseksi, ja samalla yritysten odotetaan vastaavan näihin odotuksiin vastuullisuusviestinnällään. Tämän tutkimuksen tarkoituksena oli analysoida kuluttajien turvallisuuden kokemusta sekä sitä, miten turvallisuuden kokemus heijastuu kuluttajien odotuksiin yritysten vastuullisuusviestintää kohtaan kriisiytyneessä ympäristössä. Tutkimuksen teoria perustuu kuluttajakokemuksen sekä vastuullisuusviestinnän tutkimukseen hyödyntäen psykologian ja sosiologian tieteenalojen kirjallisuutta. Tutkimusta varten toteutettiin 17 kvalitatiivista teemahaastattelua. Analyysin pohjalta kuluttajien turvallisuuden kokemus kriisiytyneessä ympäristössä koostuu viidestä ulottuvuudesta: elämän hyvinvoinnin peruspilarit, stabiilius, kontrolloitavuus, ihmisen sisäisen prosessoinnin kyvykkyys ja emotionaalinen tila. Kuluttajien turvallisuuden kokemus heijastuu myös kuluttajien odotuksiin yrityksille, eli odotukset luotettavuudesta, merkityksellisestä toiminnasta sekä nykyisen toimintaympäristön huomioonottavuudesta. Jos organisaatiot pyrkivät vastaamaan kuluttajien odotuksiin, heidän vastuullisuusviestinnässään tulisi olla elementtejä läpinäkyvyydestä, autenttisuudesta, sidosryhmälähtöisyydestä ja vakiintuneesta vastuullisuudesta. Tutkimuksella on sekä teoreettista että liikkeenjohdollista arvoa. Tutkimus toi esiin kuluttajien odotuksia yrityksille kokonaisvaltaisesti kriisiytyneessä ympäristössä sekä tarkasteli odotusten takana olevaa tekijää, kuluttajien turvallisuuden kokemusta. Lisäämällä ymmärrystä kuluttajien turvallisuuden kokemuksesta kriisien aikaan, tutkimus rikastaa kuluttaja-kokemuksen teoreettista kenttää. Lisäksi tutkimuksessa analysoitiin, miten yritysten tulisi vastata kuluttajien odotuksiin tarkastelemalla tehokkaan vastuullisuusviestintästrategian tekijöitä. Riippumatta sosiaalisen ympäristön tilasta, tehokkaat keinot odotusten vastaamiseen ovat yrityksillä samat. Nämä löydökset myös ohjaavat yritysten viestinnän ja johdon päätöksentekoa. Tutkimuksen tärkein kontribuutio on ajankohtaisen ja aikaamme värittävän ilmiön esiin nostaminen sekä tieteellisen yhteisön rohkaiseminen ilmiön tutkimiseen jatkossa.
Keywords: consumers’ experience of security, consumer expectations, CSR communications, crisis-stricken environment, kuluttajien turvallisuuden kokemus, kuluttajien odotukset, vastuullisuus-viestintä, kriisiytynyt ympäristö